ANALISIS ISOTOPI LIRIK LAGU PALETTE KARYA TOKOYAMI TOWA - Ni Wayan Meidariani; Made Agus Indra Kusumawijaya (Jurnal SORA, 2022)
Songs can be classified as literary works of the poetry genre, accompanied by music, rhythm and melody can make listeners feel as if they are in a certain atmosphere when listening to it, as is the case with the lyrics of Takoyami Towa's Palette song. This study aims to describe the results of the analysis in the form of meaning, content, themes and motifs contained in the work. The method used in this article is a qualitative method in which the data will be described in writing to find and know the meaning of each verse contained in the song, while the theory used also in this article is Greimas's Isotope theory (1983:78-81). The research was conducted to find isotopes in the lyrics of Takoyami Towa's Palette song. The end result of this article is the discovery of nine types of isotopes which are then grouped based on their respective isotopes, and two motifs found in Takoyami Towa's Palette song, namely the motives of sadness and anxiety as well as motives of motivation.